2018
DOI: 10.1186/s12918-018-0621-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hepatic one-carbon metabolism

Abstract: BackgroundThere are large differences between men and women of child-bearing age in the expression level of 5 key enzymes in one-carbon metabolism almost certainly caused by the sex hormones. These male-female differences in one-carbon metabolism are greatly accentuated during pregnancy. Thus, understanding the origin and consequences of sex differences in one-carbon metabolism is important for precision medicine.ResultsWe have created a mathematical model of hepatic one-carbon metabolism based on the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 69 publications
(96 reference statements)
1
54
0
Order By: Relevance
“…Hence, our study raises the need to adjust choline supplementation by sex, and, possibly, age. In this regard, to understand the origin and consequences of sex differences in C1-metabolism which might be important for precision medicine, Sadre-Marandi et al created a mathematical model of hepatic C1-metabolism based on physiological and biochemical female/male ratios of enzymes and metabolites of this pathway 93 . The model might be helpful in the potential application of choline supplementation, in general, and in females, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our study raises the need to adjust choline supplementation by sex, and, possibly, age. In this regard, to understand the origin and consequences of sex differences in C1-metabolism which might be important for precision medicine, Sadre-Marandi et al created a mathematical model of hepatic C1-metabolism based on physiological and biochemical female/male ratios of enzymes and metabolites of this pathway 93 . The model might be helpful in the potential application of choline supplementation, in general, and in females, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, unexplained variability can be ascribed to kidney disease, explaining a positive association between Hcy and serum creatinine [5,[16][17][18][19]. It is worth noting that men with higher muscle mass have been shown to have higher levels of both Hcy and creatinine, particularly when compared to women, given that~70% of daily SAM-dependent methylation reactions are to produce creatine [20,21]. Hcy has been positively associated with red cell distribution width (RDW) [22]; with increased serum cotinine, a measure of active or passive recent smoking [23]; and with increased liver enzyme levels [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For the effect of the intervention on CVD and heart failure/cardiac valve disease, the risks were higher in women compared to men, however, the differences were not significant. A possible greater vulnerability of women to folic acid and vitamineB12 supplementation could be explained by the influences of sex hormones in one-carbon metabolism and the differences between men and women in the expression level of enzymes in this metabolism [32].There is a gap in the knowledge of CVD in different sex and age groups, due to under-representation of women and the older population (because of higher comorbidities) [33]. It has been suggested that there is more variability of the increased risk factors by ageing, related to sex differences that could change between middle-aged and elderly adults [33].…”
Section: Discussionmentioning
confidence: 99%